A comparative analysis of the phonology and morpho-syntax of Cisukwa, Cindali and Cilambya - Mtenje, Atikonda (Linguistics, 2017)
This PhD thesis describes and compares the grammars of Cisukwa, Cindali and Cilambya (SuNdaLa) - three closely related varieties spoken in the northern region of Malawi. The analysis of the language data collected in this research project focuses on the phonological and morpho-syntactic systems of the SuNdaLa varieties by examining variation among them and by identifying the shared linguistic features. Within this research project, the linguistic distance among the three varieties has been analysed and suggestions have been made as to whether the SuNdaLa varieties should be considered as being three dialects of one language or as constituting three distinct languages. The study also places the SuNdaLa cluster into a wider context of the Bantu languages spoken in the region and more generally. Quantitative and qualitative language data was collected in the field from "native" speakers of all three varieties. The SuNdaLa survey included the collection of a comparative word list by using a questionnaire that was designed based on existing wordlists, such as „Swadesh 100 word list‟ (Swadesh 1955) as well as the SIL Comparative African Wordlist (Snider and Roberts 2006). Language data on the morpho-sytax and phonology was collected in elicitation sessions as well as by recording natural conversations among the key language consultants as well as their conversations with other community members.